Analysis of supply chain of fish captured from the Jamuna river in Bangladesh - Amin, Md Nurul; Nabi, Md Rafiqun (Research in Agriculture Livestock and Fisheries, 2019)
A study was conducted in two districts namely Bogura and Sirajgang to investigate the marketing channel and the marketing system of fishes captured from the Jamuna river in Bangladesh during a period of two consecutive years from January 2016 to December 2017. Fish captured from the Jamuna river were marketed through three types of market viz. auction market/arat, wholesale market and retail market. Operators of the fish market were the fishermen, faria, aratders, paikers or baparies, whole sellers and retailers. Ten channels were identified through which fish of the Jamuna river were shifted from the fishermen to the consumers. The shortest channel was the fishermen to consumers while the longest one was the fishermen→faria→aratders→paikers→whole seller→retailer→consumers. The highest price of fish (BDT 560/kg) was recorded for Wallago attu in retail market followed by BDT 500/kg for Tenualosa ilisha and Bagarious bagarious while, five small indigenous species (SIS) Tetraodon cutcutia, Chanda nama, Parambassis lala, Parambassis ranga, and Esomus danricus got the lowest price in retail market. Icing, weighing, transportation, capital supply were required in fish marketing channels as supporting function to overcome crisis. Major constrains prevailing in the fish marketing channels were reducing fishing areas, decreasing fish catch per day per fishermen, disturbance by illegal seasonal fishermen, lack of bargaining power and market information, lack of proper fish storage and preservation facilities in the fishing craft and fish markets, wastage of fish due to spoiling during transportation, sanitations, drainage and management problems within the market areas. Res. Agric., Livest. Fish.6(1): 133-142, April 2019